2016
DOI: 10.1016/j.joca.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 drives MMP13 expression in human osteoarthritic chondrocytes in a Klotho-independent manner

Abstract: These results demonstrate that FGF23 sustains differentiation of OA chondrocytes in a Klotho-independent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
(41 reference statements)
1
29
1
Order By: Relevance
“…Similarly, it is currently investigated, whether FGF23 can directly affect bone cells in a paracrine manner, and if so, whether this effect requires klotho or not. Interestingly, it has been shown that FGF23 can directly target chondrocytes which lack klotho, and thereby suppress proliferation and induce hypertrophy and differentiation ( 159 , 277 , 278 ). As briefly mentioned before, also macrophages and monocytes ( 215 , 216 , 244 , 245 ) as well as cells in the spleen ( 221 ) can respond to FGF23.…”
Section: Indications That Fgf23 Might Affect a Variety Of Other Tissumentioning
confidence: 99%
“…Similarly, it is currently investigated, whether FGF23 can directly affect bone cells in a paracrine manner, and if so, whether this effect requires klotho or not. Interestingly, it has been shown that FGF23 can directly target chondrocytes which lack klotho, and thereby suppress proliferation and induce hypertrophy and differentiation ( 159 , 277 , 278 ). As briefly mentioned before, also macrophages and monocytes ( 215 , 216 , 244 , 245 ) as well as cells in the spleen ( 221 ) can respond to FGF23.…”
Section: Indications That Fgf23 Might Affect a Variety Of Other Tissumentioning
confidence: 99%
“…Inhibition of pERK in cultures was able to reduce the hypertrophic induction of articular chondrocytes, in contrast to inhibition of p38 that resulted in hypertrophic induction (Prasadam et al, 2010 ). Furthermore, confirming a role for pERK in hypertrophic processes in OA chondrocytes, ERK1/2 inhibition abolished FGF23-induced MMP13 expression (Bianchi et al, 2016 ).…”
Section: Resultsmentioning
confidence: 73%
“…It has been demonstrated that the expression of FGFR1, FGF23, and its co-receptor KLOTHO is higher in OA chondrocytes compared to non-OA chondrocytes. Expression of these factors was also increased in cartilage samples with more severe macroscopic OA compared to less severe macroscopic OA within the same patient (Bianchi et al, 2016 ). Exogenous addition of FGF23 to human OA primary chondrocytes resulted in hypertrophic changes, as evidenced by COL10A1 and VEGFA induction via FGFR1 (Bianchi et al, 2016 ).…”
Section: Hypoxic and Angiogenic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…After proliferation, chondrocytes present hypertrophic morphology and secrete metal matrix proteinase to facilitate angiopoiesis and the formation of bone collar ( 3 ). However, the pathogenesis of osteoarthritis (OA) is that hyaline cartilages situated in the surface of osteoarticular manifest unbalanced homeostasis and chondrocytes differentiate into hypertrophy ( 4 , 5 ). Additionally, utilizing tissue engineering to repair cartilage defects, the regenerated cartilages are fibrocartilages and the chondrocytes from MSCs express hypertrophic marker protein ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%